2010
DOI: 10.1038/sc.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

The validity of predicting peak oxygen uptake from a perceptually guided graded exercise test during arm exercise in paraplegic individuals

Abstract: Study design: Each participant completed two submaximal, perceptually guided arm crank exercise tests and a graded exercise test (GXT) to volitional exhaustion. Objective: To assess the validity of a submaximal, perceptually guided exercise test to predict peak oxygen uptake ( . VO 2 peak) during arm cranking in paraplegic individuals. Setting: University of Jordan, Amman, Jordan. Participants: Eleven men with paraplegia as a result of poliomyelitis infection or spinal cord injury completed two submaximal perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The use of a graded exercise test to familiarise participants with RPE likely improves associations between perception of eff ort and exercise intensity, as evidenced in this study by the high correlations between RPE and measured values (power output = .98; VO 2 = .96; and HR = .95). Whilst these high correlations support other studies that have used continuous incremental protocols to establish VO 2 max in production trials ( Eston, et al , 2005 ;Lambrick, et al , 2009 ;Al-Rahamneh & Eston, 2010, graded exercise test pre-testing may not always take place when RPEs are used to prescribe exercise. Therefore, future research should look at other methods of RPE familiarisation.…”
Section: Discussionsupporting
confidence: 64%
“…The use of a graded exercise test to familiarise participants with RPE likely improves associations between perception of eff ort and exercise intensity, as evidenced in this study by the high correlations between RPE and measured values (power output = .98; VO 2 = .96; and HR = .95). Whilst these high correlations support other studies that have used continuous incremental protocols to establish VO 2 max in production trials ( Eston, et al , 2005 ;Lambrick, et al , 2009 ;Al-Rahamneh & Eston, 2010, graded exercise test pre-testing may not always take place when RPEs are used to prescribe exercise. Therefore, future research should look at other methods of RPE familiarisation.…”
Section: Discussionsupporting
confidence: 64%
“…This is in agreement with previous studies on RPE and VO 2 max prediction (AlRahamneh & Eston, 2011a, 2011bEston et al, 2005). However, unlike what AlRahamneh and Eston (2011a) found, ending the test at RPE 13 or RPE 15 results in a significant loss of accuracy in predicting VO 2 max.…”
Section: Resultssupporting
confidence: 92%
“…For this reason, heart rate may not be an accurate mean to predict VO 2 max in the SCI population. The 6-20 RPE scale has shown a strong positive correlation with RPE, heart rate, and VO 2 max in healthy populations (Al-Rahamneh & Eston, 2011a;Borg, 1982;Eston, Lamb, Parfitt, & King, 2005) and in individuals with SCI (Al-Rahamneh & Eston, 2011a, 2011b.…”
Section: Spinal Cord Injurymentioning
confidence: 95%
See 1 more Smart Citation
“…More recent studies have utilized peripheral rate of perceived exertion (RPE) as a means of estimating VO 2 peak (AlRahamneh et al 2011;Goosey-Tolfrey et al 2014), as RPE has demonstrated a linear relationship with VO 2 during arm cranking (Eston et al 1986;Borg et al 1987). While these studies cautiously concluded that RPE might be used to predict VO 2 peak, no prediction equations were provided and both studies had small sample sizes and were conducted using populations of high-level athletes with relatively high upper-limb function (Al-Rahamneh and Eston 2011;Goosey-Tolfrey, Paulson et al 2014). Previous research has demonstrated that, in the able-bodied population, active individuals show less variability in reproducing a given exercise intensity at a prescribed RPE compared to sedentary participants (Faulkner et al 2007).…”
Section: Introductionmentioning
confidence: 99%